Induction of Parturition in Cows with Misoprostol - Yildiz, Atilla (Medwell Online, 2009)
The purpose of this study, was to determine the efficacy of intravaginal misoprostol for induction of parturition in cows. Twenty-seven multiparous Holstein cows with singleton pregnancies were used in this experiment. As randomly, cows were assigned to 1 of 2 treatment groups (n = 9) and a control group (n = 9). On day 270 of gestation cows in the treatment groups were received 200 mu g or 400 mu g of misoprostol (cytotec (R)) intravaginally. Intravaginal misoprostol was given every 6 h until the onset of labour. A maximum of 6 doses was administered. The average gestation length in control cows was 281 days. All induced cows (except for one cow administered 400 mu g misoprostol) calved between 24 and 72 h after administered misoprostol. The 400 mu g dosage of misoprostol resulted in induction failures of 11.1%. The rate of placental retention, birth weights, calving difficulty and calf viability did not differ among groups. Vaginal administration of misoprostol is an effective method of inducing parturition in the cow. Misoprostol could be used to produce a predictable calving time.
Keywords: Misoprostol; induction of parturition; cow; intravaginal; labour